From Recruitment to HR to Manufacturing Outsourcing: A Narrative Research - Kar, Brajaballav; Mishra, Purna Chandra (AMC Indian Journal of Entrepreneurship, 2022)
Though the outsourcing concept and industry is a couple of decades old, the emergence of human resource outsourcing to a principal employer is a fairly recent phenomenon. In this case, human resources are provided by a third party vendor for various requirements. Earlier, non-essential services were in scope but hiring contractual employees for business critical functions such as manufacturing, quality, and others have started emerging. The functional split has created opportunity for outsourcing service providers. Various literature have argued about the pros and cons of such a practice from short and long term perspectives and mostly from the principal employers point of view. Research is inadequate from the point of view of outsourcing service provider. Through this narrative research we understand the entrepreneurial and operational perspectives of outsourcing service provider. The mismatch between the demand for skilled employees and availability creates opportunity for this sector. However, benefits to the principal employer, service provider, and employees remains a mismatch. Presence of contractual and permanent employees, salary and compensation, career progression and competency building, productivity and morale of employees are likely to become complex to manage. We call for additional research to understand the changed organisational dynamics due to this emergent practice. Entrepreneurs in this sector also need to configure their value proposition from various services and complexities involved.